2003
DOI: 10.1074/jbc.m209282200
|View full text |Cite
|
Sign up to set email alerts
|

20 S Proteasome from Saccharomyces cerevisiae Is Responsive to Redox Modifications and IsS-Glutathionylated

Abstract: The 20 S proteasome core purified from Saccharomyces cerevisiae is inhibited by reduced glutathione (GSH), cysteine (Cys), or the GSH precursor ␥-glutamylcysteine. Chymotrypsin-like activity was more affected by GSH than trypsin-like activity, whereas the peptidylglutamyl-hydrolyzing activity (caspase-like) was not inhibited by GSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 40 publications
7
85
0
4
Order By: Relevance
“…In fact, recent data suggests that the reversible S-glutathionylation of cysteine may be an important physiological regulator of the chymotrypsin-like activity (Demasi et al, 2001;Demasi et al, 2003). The current results further implicate the importance of cysteine residues for chymotrypsin-like activity by showing that the sulfhydryl-reactive compound NEM reduced degradation of both the LLVY peptide and the model substrate.…”
Section: Mechanisms Of Chymotrypsin-like Inhibitionsupporting
confidence: 74%
See 2 more Smart Citations
“…In fact, recent data suggests that the reversible S-glutathionylation of cysteine may be an important physiological regulator of the chymotrypsin-like activity (Demasi et al, 2001;Demasi et al, 2003). The current results further implicate the importance of cysteine residues for chymotrypsin-like activity by showing that the sulfhydryl-reactive compound NEM reduced degradation of both the LLVY peptide and the model substrate.…”
Section: Mechanisms Of Chymotrypsin-like Inhibitionsupporting
confidence: 74%
“…Evidence from previous studies showing partial reversal of peroxide-induced inhibition of chymotrypsin-like activity by DTT and the inhibition of chymotrypsin-like activity by sulfhydryl blocking compounds (Demasi et al, 2003;Andersson et al, 1999), suggest that at least one of the sites critical for maintenance of chymotrypsin-like activity is a cysteine residue. In fact, recent data suggests that the reversible S-glutathionylation of cysteine may be an important physiological regulator of the chymotrypsin-like activity (Demasi et al, 2001;Demasi et al, 2003).…”
Section: Mechanisms Of Chymotrypsin-like Inhibitionmentioning
confidence: 91%
See 1 more Smart Citation
“…Proteins related to cell control were also found in our study, as two clones of a proteasome component, proteolytic complexes responsible for the degradation of many cellular proteins (Demasi et al, 2003) that play an important role in regulating the cell cycle and signalling, including apoptosis and the elimination of abnormal proteins generated by mutation and oxidative damage (Berlett & Stadtman, 1997;Bochtler et al, 1999;Coux et al, 1996;Demasi et al, 2003;Giulivi et al, 1994;Ullrich et al, 1999). Moreover, proteasomes are controlled by glutathione S-transferase and the related control of oxidation-reduction reactions and production of transcription factors (Demasi et al, 2003;Silva et al, 2008).…”
Section: R Peres Da Silva and Othersmentioning
confidence: 85%
“…In addition, it was shown that reversible S-thiolation of E1 and E2 enzymes regulates the ubiquitin-dependent proteolysis in response to altered redox environment (Obin et al, 1998). Furthermore, the 20S proteasome activity in S. cerevisiae was also reported to be inhibited by S-glutathionylation following H 2 O 2 treatment (Demasi et al, 2003). These observations suggest redox regulation of the proteasome degradation machinery could regulate cyclin D1 levels.…”
Section: Intracellular Redox State and Cell Cycle Proteinsmentioning
confidence: 97%